Pemanfaatan Teknologi Informasi untuk Inovasi Motif, Diversifikasi Produk, dan Perluasan Jaringan Pasar pada Batik Nitik Kembangsore - Rianto Rianto; Enny Itje Sela; Nur Wening (I-Com: Indonesian Community Journal, 2024)
Batik Nitik Kembangsore operates in the traditional batik industry, with unique and exclusive motifs. However, the current production is limited to jarit cloth with a relatively high price, resulting in low sales turnover due to the high selling price. This Community Partnership Program proposes a solution to overcome these challenges by diversifying products and creating contemporary batik motifs using artificial intelligence. Leonardo.ai's online tools will be used to design new motifs while maintaining the aesthetic value and philosophy of Batik Nitik Kembangsore. In addition, to strengthen the marketing and sales system, the website www.kembangsore.com will be developed as an integrated digital platform. With this strategy, it is hoped that Batik Nitik Kembangsore can expand its market reach, increase competitiveness, and reach broader consumers. This innovation supports the sustainability of the traditional batik industry and strengthens Batik Nitik Kembangsore's position in the modern market.